Preparation method and application of heterogeneous Fenton-like catalyst with manganese ferrite loaded on graphene oxide-carbon nanotube composite material

By loading manganese ferrite in situ on the graphene oxide-carbon nanotube composite material, the heterogeneous Fenton catalyst is formed, which solves the problems of easy deactivation and poor stability of existing carbon-based catalysts, and achieves efficient and long-lasting wastewater treatment effects.

CN119838609APending Publication Date: 2025-04-18NANJING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411969856.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Existing carbon-based catalysts are prone to deactivate when treating wastewater, have poor stability, and are difficult to achieve a long-lasting and efficient Fenton oxidation reaction.

Method used

The graphene oxide-carbon nanotube composite material was used as the support and manganese ferrite (MnFe2O4) was loaded in situ by a one-step hydrothermal method to form a heterogeneous Fenton catalyst.

Benefits of technology

The stability and circulation performance of the catalyst are improved, the degradation capacity of organic pollutants is enhanced, and efficient wastewater treatment within a wide pH range is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838609A_ABST
    Figure CN119838609A_ABST
Patent Text Reader

Abstract

According to the graphene oxide-carbon nanotube composite material loaded manganese ferrite heterogeneous Fenton catalyst provided by the invention, manganese ferrite MnFe2O4 is loaded on a carbon nanotube CNT and graphene oxide GO in situ through a one-step hydrothermal method, and the graphene oxide-carbon nanotube composite material loaded manganese ferrite heterogeneous Fenton catalyst is applied to degradation of phenolic wastewater, so that a good treatment effect and cycling stability are achieved. According to the preparation method of the heterogeneous Fenton-like catalyst based on the dual-carbon carrier provided by the invention, the carbon nano tube and the graphene are taken as loading materials to be combined with the manganese ferrite, so that the cost is relatively low and the method is environment-friendly. And the compounding of the double-carbon carrier and the loading of manganese ferrite can be completed by a one-step hydrothermal method, the preparation steps are simple, the carbon nanotubes and graphene provide abundant specific surface areas and bear more active sites, and the catalytic performance is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wastewater treatment, and specifically relates to a preparation method of a heterogeneous Fenton-like catalyst of graphene oxide-carbon nanotube composite material loaded with manganese ferrite and application thereof. Background Art

[0002] With the development of economy and society, the discharge of industrial wastewater is increasing day by day. The impact of the difficult-to-degrade and highly toxic organic matter contained in it on the ecological environment has attracted global attention. This has made people urgently look for a safe, efficient and stable treatment technology. Heterogeneous Fenton oxidation technology has attracted wide attention in the field of wastewater treatment due to its advantages such as green and high efficiency, wide pH range of application, and easy separation of catalysts.

[0003] However, heterogeneous Fenton oxidation suffers from the sluggish regeneration kinetics of Fe(II), which means that the Fenton system cannot sustainably and rapidly generate reactive oxygen species for persistent degradation of pollutants. To overcome these inherent shortcomings, many strategies have been attempted to promote Fenton oxidation by accelerating the conversion from Fe(III) to Fe(II), mainly including external stimulation and the input of co-catalysts. In addition to the introduction of additional energy (e.g., light irradiation, electricity, and ultrasound), co-catalysts (e.g., MoS2, WS2) can also accelerate the Fe(III) / Fe(II) redox cycle. However, most previous co-catalysts (e.g., metal sulfides, hydroxylamine, and ascorbic acid) have problems such as metal ion leaching, secondary pollution, and reactive oxygen quenching, and most of the previous co-catalysts show low practical application potential. Therefore, seeking sustainable and green strategies to achieve persistent and efficient Fenton oxidation is of broad interest in environmental remediation.

[0004] In contrast, non-metallic carbonaceous materials (graphene oxide, activated carbon, carbon nanotubes, polyhydroxyfullerenes, biochar, etc.) have been widely used in heterogeneous Fenton oxidation reactions due to their rich electron content, strong adsorption, diverse structures, and abundant storage in nature. However, single carbon materials are easily deactivated after repeated use as electron sacrificial agents and cannot meet the requirements of a green and sustainable environment. Therefore, it is urgent to design and develop a carbon-based heterogeneous Fenton-like catalyst that is easy to synthesize, low-cost, green and harmless, with high catalytic performance and high stability. Summary of the invention

[0005] In view of the problem that existing carbon-based catalysts are easy to deactivate and have poor stability, the present invention provides a heterogeneous Fenton-like catalyst of manganese ferrite loaded on a graphene oxide-carbon nanotube composite material. Manganese ferrite (MnFe2O4) is in situ loaded on carbon nanotubes (CNTs) and graphene oxide (GO) by a one-step hydrothermal method, and is applied to the degradation of phenol-containing wastewater, achieving good treatment effect and cyclic stability performance.

[0006] The technical problem to be solved by the present invention is achieved through the following technical solutions.

[0007] The first aspect of the present invention provides a graphene oxide-carbon nanotube composite material supported on manganese ferrite heterogeneous Fenton-like catalyst, comprising:

[0008] Graphene oxide-carbon nanotube composite material carrier; nanoparticulate manganese ferrite active component distributed on the carbon material.

[0009] Preferably, the diameter of the carbon nanotubes is 10-20 nm, and the length of the carbon nanotubes is 10-30 μm.

[0010] Preferably, the graphene oxide is physical method few-layer graphene. The few-layer graphene has 1 to 5 layers.

[0011] Preferably, the manganese ferrite active component tightly adhered to the surface of the carbon material is in the form of nanoparticles with a diameter of about 50 to 60 nm.

[0012] The second aspect of the present invention provides a method for preparing a graphene oxide-carbon nanotube composite material supported by a manganese ferrite Fenton catalyst, comprising the following steps:

[0013] S1: Graphene is placed in a mixed solution of concentrated sulfuric acid and concentrated nitric acid with a volume ratio of 3:1 for oxidation for 1 hour to obtain graphene oxide (Go)

[0014] S2: placing carbon nanotubes and graphene oxide in a mixed solution of ferric nitrate nonahydrate and manganese nitrate tetrahydrate, stirring the mixture evenly, and then ultrasonically shaking the mixture;

[0015] S3: adjusting the pH of the mixed solution obtained in step S2 to alkaline, stirring evenly, and continuing ultrasonic shaking;

[0016] S4: transferring the mixed solution obtained in S3 to the inner lining of the reactor for hydrothermal synthesis treatment, filtering, washing, and drying the substance obtained after the hydrothermal treatment to obtain a graphene oxide-doped carbon nanotube ferrite heterogeneous Fenton catalyst;

[0017] Optionally, the specific step of S2 is: adding a carbon material with a mass ratio of CNT:GO=1:2 into a mixed solution with a molar ratio of Fe / Mn=1 / 5-1 / 2, wherein the mass concentration of ferric nitrate nonahydrate is 0.08-0.5wt%, stirring evenly for 10-30min and ultrasonically shaking for 1h, and shaking 2-5 times;

[0018] Optionally, the specific step of S3 is: continuously dropping 2 mol / L sodium hydroxide solution into the mixed solution obtained in S2, stirring continuously until pH=11, and ultrasonically shaking for 0.5 h;

[0019] Optionally, in S4, the volume of the mixed solution is 20 to 25 mL, which is transferred to the lining of the reactor and then hydrothermally synthesized at 160 to 220° C. for 12 to 28 hours. The hydrothermally synthesized material is filtered, rinsed, and dried to obtain a graphene oxide-carbon nanotube composite material loaded with manganese ferrite heterogeneous Fenton catalyst.

[0020] The third aspect of the present invention provides any one of the uses of a graphene oxide-carbon nanotube composite material loaded with a manganese ferrite heterogeneous Fenton-like catalyst in treating phenol-containing wastewater.

[0021] A specific implementation method is provided, wherein a heterogeneous Fenton-like catalyst is premixed with phenol-containing wastewater for 5 to 10 minutes and then hydrogen peroxide (H2O2) is added;

[0022] Preferably, the dosage of the heterogeneous Fenton-type catalyst is 0.1 to 1 g / L, and the dosage of hydrogen peroxide is 0.007 to 0.35 g / L;

[0023] Preferably, according to different types of phenol-containing wastewater, the normal time for oxidative removal of organic matter is 0.25 to 1 hour.

[0024] Compared with the prior art, the present invention has significant advantages:

[0025] (1) Metal doping is one of the commonly used modification methods for manganese ferrite. The preparation process is usually complicated, the economic cost of doping with rare metals is too high, and metal leaching is prone to secondary pollution when the amount of doped metal is small. The present invention provides a dual non-metallic carrier doping method, which combines carbon nanotubes and graphene oxide as support materials with manganese ferrite, while improving the catalytic ability, reducing the problem of metal loss, and is low in cost and environmentally friendly.

[0026] (2) The graphene oxide-carbon nanotube composite material provided by the present invention is loaded with a heterogeneous Fenton-like manganese ferrite catalyst. The carbon material itself has a strong electron supply capacity, which can promote the reduction of Fe(III) to Fe(II) and accelerate the redox cycle of iron. On the other hand, due to the difference in electron density between carbon nanotubes and graphene oxide, the composite material produces an electron-rich region at the interface, which increases the oxidation potential of Fe(III) and enhances the reaction between Fe(III) and H2O2. The iron metal site can continuously obtain electron-activated H2O2, promote the formation of ·OH, thereby improving the catalyst's ability to degrade organic pollutants and the catalyst cycle performance.

[0027] (3) The present invention uses a one-step hydrothermal method to complete the synthesis of manganese ferrite and the loading of the dual-carbon material composite. The preparation steps are simple, and the optimal ratio of carbon nanotubes and graphene can provide abundant specific surface area, carry more active sites, and further improve the catalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is the XRD pattern of the graphene oxide-carbon nanotube composite material loaded with manganese ferrite heterogeneous Fenton catalyst prepared in Example 1.

[0029] Figure 2 This is a scanning electron microscope (SEM) image of the graphene oxide-carbon nanotube composite material loaded with manganese ferrite heterogeneous Fenton catalyst prepared in Example 1.

[0030] Figure 3 This is an element mapping scan of the graphene oxide-carbon nanotube composite material loaded with manganese ferrite heterogeneous Fenton catalyst prepared in Example 1.

[0031] Figure 4 This is the full XPS spectrum of the graphene oxide-carbon nanotube composite material supported on the manganese ferrite heterogeneous Fenton catalyst prepared in Example 1.

[0032] Figure 5 This is the Fe2p XPS fine spectrum of the graphene oxide-carbon nanotube composite material supported on the manganese ferrite heterogeneous Fenton catalyst prepared in Example 1.

[0033] Figure 6 This is the effect diagram of treating phenol wastewater with catalysts with different Fe / Mn ratios.

[0034] Figure 7 This is the effect diagram of treating phenol wastewater with catalysts with different CNT / Go ratios.

[0035] Figure 8 This is a diagram showing the pollutant removal effect of the catalyst at different pH values.

[0036] Fig. 9 This is the performance diagram of the catalyst in the cycle experiment.

[0037] Fig.10 It is a curve diagram of the relationship between the removal rate of comparative example 1 and embodiment 1 changing with time.

[0038] Fig.11 This is the performance diagram of the cycle experiment of Comparative Example 2. DETAILED DESCRIPTION

[0039] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.

[0040] The present invention provides a graphene oxide-carbon nanotube composite material supported manganese ferrite heterogeneous phase Fenton catalyst, comprising:

[0041] Carbon nanotube carrier; graphene oxide carrier; nano-particle manganese ferrite active component distributed on the carbon material. The diameter of the carbon nanotube is 10-20nm, and the length of the carbon nanotube is 10-30μm. Graphene oxide is a physical method few-layer graphene. The few-layer graphene is 1-5 layers. The manganese ferrite active component tightly adhered to the surface of the carbon material is in the form of nanoparticles with a diameter of about 50-60nm.

[0042] In addition, a method for preparing a graphene oxide-carbon nanotube composite material-supported manganese ferrite heterogeneous Fenton catalyst is specifically provided, comprising the following steps:

[0043] S1: oxidizing graphene in a mixed solution of concentrated sulfuric acid and concentrated nitric acid and then washing with ultrapure water until neutral to obtain graphene oxide (Go);

[0044] S2: placing carbon nanotubes and graphene in a mixed solution of iron nitrate nonahydrate and manganese nitrate tetrahydrate, stirring evenly, and then ultrasonically vibrating;

[0045] S3: adjusting the pH of the mixed solution obtained in step S2 to alkaline, stirring evenly, and continuing ultrasonic shaking;

[0046] S4 transfers the mixed solution obtained in S3 to the inner lining of the reactor for hydrothermal synthesis treatment, and filters, rinses and dries the substance obtained after the hydrothermal treatment to obtain a graphene oxide-carbon nanotube composite material loaded with manganese ferrite heterogeneous Fenton catalyst.

[0047] Based on the above content, specific embodiments and experiments are provided as follows:

[0048] Example 1

[0049] The preparation of the heterogeneous Fenton catalyst of graphene oxide-carbon nanotube composite material supported by manganese ferrite comprises the following steps:

[0050] S1 prepares a mixed solution of concentrated sulfuric acid and concentrated sulfuric acid in a volume ratio of 3:1, places the physical method few-layer graphene into the mixed solution and oxidizes it at 50°C for 1 hour to obtain graphene oxide;

[0051] S2: Prepare 20 mL of a mixed solution of 0.25 wt% ferric nitrate nonahydrate and 0.62 wt% manganese nitrate tetrahydrate, add 50 mg of carbon material (CNT:GO=1:2) into the mixed solution, stir evenly for 10 min, and oscillate under ultrasound for 1 h;

[0052] S3: 2 mol / L sodium hydroxide solution was continuously added to the mixed solution obtained in S2, and the mixture was stirred continuously until the pH value was 11, and ultrasonically vibrated for 0.5 h;

[0053] S4: transferring the mixed solution obtained in S3 to the inner lining of a reactor and then performing hydrothermal synthesis at 200° C. for 20 h; filtering, rinsing, and drying the substance obtained after the hydrothermal treatment to obtain a graphene oxide-carbon nanotube composite material loaded with manganese ferrite heterogeneous Fenton catalyst (MnFe2O4-CNT / GO).

[0054] Characterization of the heterogeneous Fenton catalyst of graphene oxide-carbon nanotube composite supported on manganese ferrite prepared in Example 1

[0055] XRD results show that ( Figure 1 ) showed that the characteristic diffraction peaks of the cubic spinel structure MnFe2O4 (111), (220), (311), (222), (400), (422), (511) and (440) crystal planes appeared at 18.1°, 29.9°, 33.6°, 36.1°, 43.2°, 54.1°, 57.3° and 63.2°, respectively. Compared with Fe2O3, the corresponding and different peaks were obvious, which proved the successful preparation of MnFe2O4-CNT / GO composite catalytic material.

[0056] SEM images( Figure 2 ) showed that GO has a skeleton support role, there are well-dispersed CNT bridges between its layers, and the active components (MnFe2O4) are evenly distributed on graphene and carbon nanotubes;

[0057] Mapping Figure 3 ) showed that the prepared catalyst (MnFe2O4-CNT / GO) contained four elements: C, O, Fe, and Mn, with reported mass concentrations of 73.63%, 20.18%, 2.65%, and 3.54%, respectively. The active component (MnFe2O4) was evenly distributed on the carbon material;

[0058] XPS results ( Figure 4 ) showed that the prepared catalyst (MnFe2O4-CNT / GO) contained four elements: Fe, Mn, O, and C;

[0059] Fe 2p fine map ( Figure 5 ) shows that the characteristic peaks at 724.56 and 710.95 eV correspond to the Fe2p1 / 2 and Fe 2p3 / 2 spin orbits, respectively. The Fe 2p3 / 2 region can be decomposed into two binding energy peaks at 712.08 and 710.56 eV, corresponding to the Fe at the tetrahedral position, respectively. 3+ and Fe in the octahedral position 2+ , indicating that divalent and trivalent iron exist at the same time. In addition, there are two satellite peaks at 733.09 and 718.77 eV, which also indicates that Fe 3+ The existence of species.

[0060] Example 2

[0061] Experiment on the optimal iron-manganese ratio of graphene oxide-carbon nanotube composite material supported on manganese ferrite heterogeneous Fenton catalyst.

[0062] Taking the preparation method of MnFe2O4-CNT / GO in Example 1 as an example, the amount of ferric nitrate nonahydrate was not changed, but the amount of manganese nitrate tetrahydrate was changed to make the iron-manganese molar ratio 1:2, 1:3, 1:4, and 1:5, hydrogen peroxide (H2O2) was used as the oxidant, and phenol was the phenol-containing wastewater pollutant, and the degradation effect of the catalyst was explored.

[0063] The catalyst dosage is 0.3 g / L, the hydrogen peroxide dosage H2O2 is 10 mmol / L, the organic pollutant concentration is 20 mg / L, and the total treatment time of the oxidation system is 15 min.

[0064] The removal rate of catalysts with different iron-manganese ratios is shown in the figure below. Figure 6 As shown in the figure, phenol was rapidly degraded within 15 min. For catalysts with different iron-manganese ratios, the phenol removal rates were all higher than 90%, among which the catalyst removal rate of Fe:Mn=1:4 was close to 100%. Therefore, the optimal iron-manganese ratio of the graphene oxide-carbon nanotube composite material loaded with manganese ferrite heterogeneous Fenton catalyst is 1:4.

[0065] Example 3

[0066] Experiment to explore the optimal ratio of graphene oxide-carbon nanotube composite materials.

[0067] Taking the preparation method of MnFe2O4-CNT / GO in Example 1 as an example, the total amount of carbon nanotubes and graphene (50 mg) was not changed, and the CNT:Go molar ratio was 3:1, 2:1, 1:1, and 2:1. Other conditions remained unchanged. Hydrogen peroxide (H2O2) was used as the oxidant and phenol was used as the characteristic pollutant to explore the optimal ratio of carbon nanotubes and graphene.

[0068] The catalyst dosage is 0.3 g / L, the hydrogen peroxide dosage H2O2 is 10 mmol / L, the organic pollutant concentration is 20 mg / L, and the total treatment time of the oxidation system is 15 min.

[0069] The catalyst removal rate of different carbon nanotubes and graphene ratios is shown in the figure Figure 7 As shown in the figure, phenol was rapidly degraded within 15 minutes. For different catalysts, the phenol removal rate was higher than 80%, among which the catalyst removal rate of CNT:Go=1:2 was close to 100%, so the optimal ratio of graphene oxide-carbon nanotube composite material was 1:2.

[0070] Example 4

[0071] Taking MnFe2O4-CNT / GO prepared in Example 1 as catalyst, H2O2 as oxidant, and phenol as phenol pollutant, the effect of pH on the degradation of phenol in the MnFe2O4-CNT / GO / H2O2 system was investigated.

[0072] Reaction conditions: catalyst = 0.3g / L, hydrogen peroxide = 10mmol / L, organic pollutant concentration = 20mg / L, total treatment time of oxidation system is 15min, degradation results are as follows Figure 8 As shown in the figure, when the pH is low, the degradation rate of phenol is fast, and the removal rate reaches 100%. As the pH increases to neutral to alkaline, the degradation rate of phenol gradually slows down, but after 15 minutes of reaction, the degradation rate is still about 70%, indicating that MnFe2O4-CNT / GO has good removal ability under a wide pH range.

[0073] Example 5

[0074] Using the MnFe2O4-CNT / GO prepared in Example 1 as a catalyst, H2O2 as an oxidant, and phenol as a typical phenolic pollutant, an experiment was conducted to explore the stability and cycle performance of MnFe2O4-CNT / GO.

[0075] Under the experimental conditions of the above-mentioned experiment on the optimal iron-manganese ratio of graphene oxide-carbon nanotube composite material supported on manganese ferrite heterogeneous phase Fenton catalyst, 10 cycles of experiments were carried out, and the results are as follows Fig. 9 As shown, the catalytic performance of the catalyst has not been significantly reduced, and the removal rate can still reach more than 97%, indicating that the catalyst has good stability and recyclability.

[0076] Comparative Example 1

[0077] The effect of adding graphene oxide on the synthesis catalyst was not investigated.

[0078] The other conditions of the heterogeneous Fenton-like catalyst prepared in this comparative example are consistent with those in Example 1, with the only difference being that graphene is not added in the preparation step S1, and carbon nanotubes of the same mass are used instead of graphene.

[0079] Phenol was degraded according to the procedure of Example 2. Fig.10As shown, the catalyst (MnFe2O4-CNTs) prepared in Comparative Example 1 has a phenol removal rate of 91% within 15 minutes. The reduction in removal rate is because when graphene is not added, the specific surface area of ​​the catalyst carrier is reduced, the catalytic active sites are reduced, and the oxidation potential of Fe(III) is not enhanced, the reduction rate of Fe(III) is slowed down, and thus the catalytic reaction rate is slowed down. On the contrary, the addition of graphene can not only increase the specific surface area of ​​the catalyst carrier and increase the active sites, but also enhance the oxidation potential of Fe(III), continuously obtain electrons from H2O2, continuously activate hydrogen peroxide to produce hydroxyl radicals, and thus speed up the reaction rate.

[0080] Comparative Example 2

[0081] The heterogeneous Fenton-like catalyst prepared in this comparative example is consistent with that in comparative example 1, and the cyclic stability performance of a single carbon carrier is explored.

[0082] Under the experimental conditions of the above-mentioned experiment on the optimal iron-manganese ratio of graphene oxide-carbon nanotube composite material supported on manganese ferrite heterogeneous phase Fenton catalyst, 10 cycles of experiments were carried out, and the results are as follows Fig.11 As shown, the catalytic performance of the catalyst is significantly lower than that of the stability and cycle performance experiments of MnFe2O4-CNT / GO, and the removal rate decreases after ten cycles, indicating that a single carbon carrier catalyst does not have good cycle stability performance.

Claims

1. A graphene oxide-carbon nanotube composite material supported on manganese ferrite heterogeneous Fenton catalyst, characterized in that: include: The catalyst comprises a carbon nanotube carrier, a graphene oxide carrier, and a nano-granular manganese ferrite active component distributed on the carbon material.

2. The graphene oxide-carbon nanotube composite material supported manganese ferrite heterogeneous Fenton catalyst according to claim 1, characterized in that: The diameter of carbon nanotubes is 10 to 20 nm, and the length of carbon nanotubes is 10 to 30 μm.

3. The graphene oxide-carbon nanotube composite material supported manganese ferrite heterogeneous Fenton catalyst according to claim 1, characterized in that: Graphene oxide is a physical few-layer graphene, and the few-layer graphene has 1-5 layers.

4. The graphene oxide-carbon nanotube composite material supported manganese ferrite heterogeneous Fenton catalyst according to claim 1, characterized in that: The manganese ferrite active component tightly adhered to the surface of the carbon material is in the form of nanoparticles with a diameter of about 50 to 60 nm.

5. A method for preparing a heterogeneous Fenton catalyst supported on a graphene oxide-carbon nanotube composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1: Graphene is placed in a mixed solution of concentrated sulfuric acid and concentrated nitric acid for oxidation for 1 hour, then washed with ultrapure water until neutral and freeze-dried to obtain graphene oxide; S2: placing carbon nanotubes and graphene in a mixed solution of iron nitrate nonahydrate and manganese nitrate tetrahydrate, stirring evenly, and then ultrasonically vibrating; S3: adjusting the pH of the mixed solution obtained in step S2 to alkaline, stirring evenly, and continuing ultrasonic shaking; S4 transfers the mixed solution obtained in S3 to the inner lining of the reactor for hydrothermal synthesis treatment, and filters, rinses and dries the substance obtained after the hydrothermal treatment to obtain a graphene oxide-carbon nanotube composite material loaded with manganese ferrite heterogeneous Fenton catalyst.

6. The method for preparing the graphene oxide-carbon nanotube composite material supported manganese ferrite heterogeneous Fenton catalyst according to claim 5, characterized in that: The following steps are involved: The specific steps of S1 are: adding a carbon material with a mass ratio of CNT:GO=1:2 into a mixed solution with a molar ratio of Fe / Mn=1 / 5~1 / 2, stirring evenly for 10~30min and ultrasonically oscillating for 1h, with the oscillation times being 2~5 times, wherein the mass concentration of ferric nitrate nonahydrate is 0.08~0.5wt%.

7. The method for preparing the graphene oxide-carbon nanotube composite material supported manganese ferrite heterogeneous Fenton catalyst according to claim 5, characterized in that: The specific steps of S2 are: continuously adding 2 mol / L sodium hydroxide solution to the mixed solution obtained in S1, stirring continuously until the pH is 11, and ultrasonically shaking for 0.5 h.

8. The method for preparing the graphene oxide-carbon nanotube composite material supported manganese ferrite heterogeneous Fenton catalyst according to claim 5, characterized in that: In S3, the volume of the mixed solution is 20-25 mL. After being transferred to the inner lining of the reactor, it is hydrothermally synthesized at 160-220° C. for 12-28 h. The hydrothermally synthesized material is filtered, rinsed, and dried to obtain a graphene oxide-carbon nanotube composite material loaded with manganese ferrite heterogeneous Fenton catalyst.

9. Use of the graphene oxide-carbon nanotube composite material supported on manganese ferrite heterogeneous Fenton catalyst according to any one of claims 1 to 4 in treating phenol-containing wastewater.

10. Use of the graphene oxide-carbon nanotube composite material supported on manganese ferrite heterogeneous Fenton catalyst in treating phenol-containing wastewater according to claim 9, characterized in that: The specific application is: graphene oxide-carbon nanotube composite material loaded with manganese ferrite heterogeneous Fenton catalyst is pre-mixed with phenol-containing wastewater for 5 to 10 minutes and then hydrogen peroxide H2O2 is added; the catalyst dosage is 0.1 to 1 g / L, and the hydrogen peroxide dosage is 0.007 to 0.35 g / L; according to different types of phenol-containing wastewater, the organic matter oxidation removal time is 0.25 to 1 hour.